A Study on the Pragmatic Functions of Parang in Tagalog Utterances - Tan, Briar Rose V. (The Archive, 2024)
This paper is a preliminary exploration of the functions of parang to understand its usage by Tagalog speakers. The study aims to bring attention to its potential as a discourse marker in the language. The data for the analysis is derived from short interviews which are the basis of the language corpus. The observed multifunctionality of parang is categorized into nine main variations: to express comparison, a discourse marker, an evidential marker, as a filler word, approximation, to paraphrase, a quotative device, and as a way to soften direct comments or opinions. Frequency and distribution of usage is linked to age and generational differences. Initial hypothesis suggests that discourse markers are predominantly utilized by the younger generation but it is also being used by older individuals upon closer investigation.